Development of Mitochondrial Activities in Pea Cotyledons during and following Germination of the Axis - Morohashi, Yukio (1980)
Development of mitochondrial activities in pea cotyledons during early times after the start of imbibition occurred in two phases. In the first phase (0 to 8 hours after the start of imbibition), succinate or NADH oxidation increased rapidly, while malate or α-ketoglutarate oxidation remained low. The latter activities developed only 8 to 12 hours after the start of imbibition (the second phase). Development in the first phase was induced by water uptake, but some development occurred even when the cotyledons were fully imbibed. The presence of the axis was required for the second phase of the development. It is suggested that mitochondrial development in the second phase is brought about by activation of the electron transfer path at a site between the oxidation of endogenous NADH and the reduction of ubiquinone.